Novel classification for simple peripheral arteriovenous malformations based on anatomic localization: Prevalence data from the tertiary referral center in China - Shen, Yuchen; Wang, Zhenfeng; Yang, Xitao; Zheng, Lianzhou; Wen, Mingzhe; Han, Yifeng; Li, Xiao; Zhang, Liming; Wang, Jingbing; You, Jianxiong; Jiang, Chunyu; Su, Lixin; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: In absence of the large-sample study of simple peripheral arteriovenous malformation (pAVM), we aimed to perform the epidemiological analysis of over 1,000 simple pAVM patients from our center in the past five years, and establish a novel classification based on the anatomical localization of the primary lesion. Results: Between March 27, 2016, and March 31, 2021, Chinese patients who were diagnosed with simple pAVM were taken into account. Those who suffered from simple cnsAVM, combined type of AVM, and syndromes, such as CLOVES syndrome, etc. were all excluded from this study. A total of 1070 simple pAVM patients were screened out. All of the simple pAVM patients were diagnosed by clinical manifestations and imaging examinations. Demographic data were obtained from the National Bureau of Statistics of China. The 5-year prevalence of simple pAVM was about (2.15-6.60) /1,000,000 population. The male-female ratio was approximately 1.22:1. The pAVM inpatients that were included in the age group of 21 30 years old had the highest constituent ratio (P = 0.01). The classification included four groups: Type Ⅰ (primarily occurring in soft tissue); Type Ⅱ (primarily occurring in bone); Type Ⅲ (primarily occurring in the viscus) and Type Ⅳ (simple pAVM coexisting with CNS lesions). There were two subtypes of Type Ⅰ: the A subtype (involving one major anatomical region) and the B subtype (involving two or more major anatomical regions); two subtypes of Type Ⅱ: the A subtype (the cortex was intact) and the B subtype (the lesion had broken through the cortex). Generally, 657 patients were classified as Type ⅠA (61.4%), 230 patients were Type ⅠB (21.7%), 82 patients were Type ⅡA (7.7%) and 79 were categorized as Type ⅡB (7.4%); the number of patients who had Type Ⅲ and Type Ⅳ pAVM were 9 (0.8%) and 11 (1.0%), respectively. The clinical manifestations and diagnostic standards for each type were also systematically summarized. Conclusions: Prevalence data for simple pAVMs were analyzed, and a novel classification for simple pAVMs was proposed based on the anatomy of the lesions. The present work was expected to facilitate the diagnosis of simple pAVM in clinical works.